2001
DOI: 10.17741/bgsf/73.1-2.003
|View full text |Cite
|
Sign up to set email alerts
|

Eastern margin of the Vaasa Migmatite Complex, Kauhava, western Finland: preliminary petrography and geochemistry of the diatexites

Abstract: Extensive biotite diatexites resembling S-type granitoids occur in the eastern part of the Vaasa Migmatite Complex (VMC, 1.89 Ga, 6000 km 2 ) at Kauhava, western Finland. These rocks have undergone a textural homogenization that has destroyed the primary bedding. Pre-migmatization structures are preserved only in inclusions. The diatexites are clearly peraluminous and have relatively high concentrations of TiO 2 (0.7-0.9 wt%), CaO (2.4-3.0 wt%) and total of Fe 2 O 3 tot + MgO (6.6-8.8 wt%). The contact of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 22 publications
(19 reference statements)
0
12
0
Order By: Relevance
“…Based on field work and petrological and geochemical observations of the VMC granitoids in the inner part and the surrounding migmatites and schists in the outer part, Mäkitie () suggested that the granitic rocks represent in situ melting of the adjacent sedimentary rocks. This is supported by the similar inherited U‐Pb ages, the initial Nd isotopic composition of the granitoids, and the surrounding metasediments (Kotilainen et al, ; Suikkanen et al, ).…”
Section: Geological and Geophysical Settingmentioning
confidence: 99%
“…Based on field work and petrological and geochemical observations of the VMC granitoids in the inner part and the surrounding migmatites and schists in the outer part, Mäkitie () suggested that the granitic rocks represent in situ melting of the adjacent sedimentary rocks. This is supported by the similar inherited U‐Pb ages, the initial Nd isotopic composition of the granitoids, and the surrounding metasediments (Kotilainen et al, ; Suikkanen et al, ).…”
Section: Geological and Geophysical Settingmentioning
confidence: 99%
“…The batholith, together with the surrounding metasediments, comprises the Vaasa complex. The boundary between the granitoids of the Vaasa batholith and the schists of the Bothnian Belt is gradual through metatexites and diatexites (Mäkitie et al, 2012) with no observed intrusive contacts (Mäkitie et al, 1999;Mäkitie, 2001;Lehtonen et al, 2005;Sipilä et al, 2008). In fact, the boundary area is texturally, mineralogically, and geochemically continuous (Mäkitie et al, 2012).…”
Section: Geologic Settingmentioning
confidence: 99%
“…In fact, the boundary area is texturally, mineralogically, and geochemically continuous (Mäkitie et al, 2012). This has led many workers to consider the granitoids of the Vaasa complex to represent in situ melting (e.g., Mäkitie, 2001;Sipilä et al, 2008;Mäkitie et al, 2012).…”
Section: Geologic Settingmentioning
confidence: 99%
See 1 more Smart Citation
“…First, there are numerous examples of terranes preserving voluminous amounts of segregated former granitic liquids that apparently did not leave the deep-crustal environment as liquids (Percival, 1991;Jung et al, 2000;Makitie, 2001;Redler et al, 2013). If melt is readily extractable in small volumes, the large amounts of leucosome in some migmatities (metatexites and diatexites) would have to represent either partial melts arrested in a state of incomplete escape or liquids from a foreign source arrested in transit through a terrane undergoing high grade metamorphism, with or without partial melting.…”
Section: The Problem Of the Extractability Of Granitic Partial Meltmentioning
confidence: 99%